Especificidade de um Jogo e de um processo de Treino no contexto do Futebol Feminino: Análise do pressing defensivo da equipa - Cristiano Filipe Silva Robalinho (2018)
The football game is an unique and incomparable sport phenomenon, either because of it own nature or because the passion that moves people. It was this same passion and the ambition of understanding better it nature in a specific context, such as Women's Football, the main reasons that led to the accomplishment the professional intership, in the scope of the 2nd Degree of High Performance in Sport at the Faculty of Sport of the University of Porto.The purpose of the internship is to acquire a set of knowledge and skills related to the game and the training process. At this level, it is possible to understand the importance and the proposes of planning and structuring the contents and the principles of the training session and of the weekly planning, according to the game idea that the coach intends to implement.The operationalization of this idea is a process that aims to shape the training and the exercises so that the players demonstrate, in the game, the desired behaviors. For this, it is crucial that the training presents the Specificity and the Representability necessary for the construction and evolution of these behaviors.The tasks performed included the planning and operationalization of the training process, with a focus on defensive behaviors, especially at the pressing level. At this level, the defensive behaviors performed by the players were studied and analyzed during four months, either in the training process, through reduced games and situations of possession of the ball, or in the competitive context. These have been determining to increasing the levels of competitiveness, intensity and commitment, as well as improving the results achieved.In general, this professional internship reports the importance of the presence and construction of a Game Model that considers the competitive and institutional context, the characteristics of the players and the coach´s convictions. In addition, it also reflects the importance of creating competitive situations in the training process and, finally, the characteristics, difficulties and variations founded in this context of Women's Football.